The lost city of Z : a tale of deadly obsession in the Amazon - Grann, David (Vintage Books, 2010)
In 1925, the legendary British explorer Percy Fawcett ventured into the Amazon jungle, in search of a fabled civilization. He never returned. Over the years countless perished trying to find evidence of his party and the place he called "The Lost City of Z." --from publisher description